(untitled) (Research, Society and Development, 2018)
Acknowledging the importance of knowing how to think and its methods to draw a parallel between the forms of reasoning accompanying cognitive changes in the human mind and the methodological models to plan and execute scientific research was the objective of this study. We analyzed articles and publications that brought in their scope both the phases of reasoning and methods, as well as age differences in cognition, critical and analytical thinking development. As we can see, studies still need to advance from the perspective of logical reasoning in adults, since there are enough material contemplating studies in children and adolescents. However, we have sufficient grounds to declare that such sophisticated reasoning that the adult mind produces is complex and complete enough to be matured and necessary to scientific research.